“Looking Out for Each Other”: Street-Involved Youth’s Perspectives on Friendship - Werdal, Thayne; Mitchell, Lisa M. (Anthropologica, 2018)
In public discourses, friendships among street-involved youth are often regarded as sources of delinquent or risky behaviour. Through interviews with street-involved youth in Victoria, BC, we explore youth’s ideas about their friendships. Our analysis suggests that the youth we interviewed have created a “relational refuge,” that is, a social space and metaphorical home constituted through trust, proximity, and sharing of emotions and resources. Our research highlights how friendships can mediate some of the harmful aspects of street life for youth by enabling collective forms and practices of generalised reciprocity, acceptance and collaboration.